Women Rape Survivors Narratives of Psychological Support and Counselling Experiences - Vieweger, Maria (Department of Psychology, 2020)
South Africa has one of the highest rates of rape in the world. Experiencing rape frequently proposes substantial consequences on survivors’ physical, psychological and social wellbeing, which accentuates the importance of providing survivors with help, support, and protection. However, the scarce studies examining survivors’ experiences with the support system indicate many flaws within the system, sometimes even resulting in further harm. This failure of governmental support systems stimulated an increasing manifestation of NGOs as providers of survivor support. It is consequently crucial to understand and evaluate the success of these services to fully understand the quality of available support. The objective of this study was to investigate women rape survivors’ post rape experiences and their journey and subsequent experiences with the counselling provided to them by the Cape Town based NGO Rape Crisis. Fifteen adult rape survivors were recruited via opportunity sampling and asked to participate in one hour long unstructured interviews. In line with the research topic and the research questions, an intersectional feminist paradigm was chosen for the theoretical framework and thematic narrative analysis was applied as the analytic approach. The analysis showed four themes relating to rape survivors’ narratives on post-rape challenges, namely; the silence and stigma that victimises survivors, the psychological effects of rape, help seeking as a last resort, and demystifying counselling. Additionally, five themes around survivors’ experiences of Rape Crisis counselling were established, namely; the value of a professional safe space, building a counsellor relationship, talking and listening, a collaborative effort to finding oneself, and sharing collective stories of pain. The findings highlight the need for more outreach and education efforts around rape, as well the importance for professional yet not too clinical psychological support which incorporates empowerment principles and focuses on help to self-help.